Strategi Komunikasi Pemasaran Pada Konten Media Sosial Instagram Coffee Shop @titikkoma.solobaru - Alfaridzi, Afran Dafa; Suryo Sarjono, Herning; Itasari, Andri Astuti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The presence of Instagram as one of the social media platforms that has the most users in Indonesia, making Instagram a social media platform that has quite a big influence in the field of digital marketing communications. This research aims to analyze marketing communication strategies on content contained on social media Instagram Coffee Shop Titik Koma Solo Baru, @titikkoma.solobaru. The marketing communication strategy on social media content Instagram @titikkoma.solobaru was analysed using the theory from Kotler (2017), regarding the content marketing communication strategy which consists of 8 stages, namely Defining objectives, Segmenting audiences, Planning content, Creating content, Distributing content, Amplifying content, Evaluating content, and Improving content. This research is a qualitative descriptive study, which uses data collection techniques in the form of interviews and documentation. From the research results it can be concluded that the marketing communication strategy on the social media Instagram @titikkoma.solobaru is implemented neatly and conceptually, in accordance with the theory used.